1998
DOI: 10.1177/0013164498058002012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Shortened form of the Fennema-Sherman Mathematics Attitudes Scales

Abstract: Data from 196 Irish school children were analyzed using principal components analysis with a varimax rotation to determine whether the underlying factor structure of the Fennema-Sherman Mathematics Attitudes Scales (FSMAS) fit the dimensions suggested by the position of the 108 items on nine subscales. Results indicated a factor structure virtually identical to a previous study that used a different sample, with the items being reduced to six separate components rather than nine as suggested by the scales' dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 15 publications
3
75
1
5
Order By: Relevance
“…To explore the characteristics of the current sample, we used the same factor analysis method employed by Mulhern and Rae (1998) to compare their results with those of the present study. Both studies identified six factors, and the percentages of variance accounted were 45.7% in Mulhern and Rae and 41.5% for the present study.…”
Section: Comparison Of Factor Analytic Results Between Previous and Pmentioning
confidence: 99%
See 4 more Smart Citations
“…To explore the characteristics of the current sample, we used the same factor analysis method employed by Mulhern and Rae (1998) to compare their results with those of the present study. Both studies identified six factors, and the percentages of variance accounted were 45.7% in Mulhern and Rae and 41.5% for the present study.…”
Section: Comparison Of Factor Analytic Results Between Previous and Pmentioning
confidence: 99%
“…Because the BI methods presented below use the trace information criterion directly, they do not depend on any secondary results as is the case when employing Mulhern and Rae's (1998) factor analysis method. Details on this point are presented in the discussion section.…”
Section: Trace Informationmentioning
confidence: 99%
See 3 more Smart Citations